Safety of dabigatran in patients with atrial fibrillation and chronic kidney disease: pharmacokinetic and pharmacogenetic aspects - A. I. Skripka (Медицинский совет, 2020)
Background: despite well-studied safety profile of dabigatran its interactions with genetic polymorphism parameters are poorly understood, especially in patients with moderate chronic kidney disease (CKD). This study was aimed to evaluate relationships between CES1 and ABCB1 polymorphism, dabigatran trough plasma concentration (DTPC) and bleeding events in patients with AF and CKD.Methods: patients with atrial fibrillation (AF) and stage 3 CKD treated with dabigatran 110mg or 150 mg have been included in the study. Real-time PCR was used to evaluate single nucleotide polymorphisms (SNPs) of the ABCB1 gene (rs1045642, rs4148738) and CES1 gene (rs2244613). A plasma trough concentration/dose (C/D) ratio was used as a pharmacokinetic index.Results: a total of 60 patients, aged 51–89 years (median age 76 years) were evaluated. Compared with patients given 150 mg twice a day, those given 110 mg twice a day were older (79 vs 67.5, p < 0.0001) and had lower creatinine clearance (CrCl) (50.5 vs 60.5 mL/min/1.73 m2, p = 0.015). We found C/D values to have high interindividual variability (mean 365.9 ± 290.4 μg/ml: mg/day, range 23.64-1452.73). Individuals with CKD 3B had higher concentration of dabigatran compared with those with 3A stage (488.7 ± 232.3 vs 332 ± 297.8 μg/ml : mg/day, p = 0.02). Consequently, there also was negative correlation of C/D with CrCl (r = -0.4, p = 0.0015). Evaluated SNPs (rs1045642, rs4148738, and rs2244613) did not affect C/D values (H test p > 0.05).Conclusions: C/D values were significantly higher in patients with CKD 3B stage and those treated with dabigatran 110 mg. There was no influence of aforementioned SNPs on dabigatran trough concentrations and clinical outcomes.